Consumption patterns and diet gaps across regional Myanmar - Scott, J.M.; Mahrt, Kristi; Thilsted, Shakuntala H. (2021)
Transformation of Rural Landscapes for Sustainable and Nutritious Food Systems is a project that attempts to understand the geographic disparities in both diets and agricultural production systems in Myanmar. Its aim is to devise plausible approaches for environmentally sustainable nutrition-sensitive agriculture under existing conditions as well as possible climate-altered conditions in the future. The project analyzes secondary data at the state and regional level across Myanmar. This technical report presents the findings of a diet analysis based on the Integrated Household Living Conditions Assessment Survey (IHLCA) 2010. The aim of the nutrition component of the study is to understand current diet patterns in Myanmar to determine what makes up the typical local diet and identify what the diet gap is in each location.